Purification, characterization and partial sequence of a pro‐inflammatory lectin from seeds of Canavalia oxyphylla Standl. & L. O. Williams. Issue 3 (16th January 2014) - Santiago, Mayara Q.; Leitão, Cintia C. F.; Pereira‐Junior, Francisco N.; Pinto‐Junior, Vanir R.; Osterne, Vinicius J. S.; Lossio, Claudia F.; Cajazeiras, João B.; Silva, Helton C.; Arruda, Francisco V. S.; Pereira, Livia P.; Assreuy, Ana M. S.; Nascimento, Kyria S.; et al.
<x xml:space="preserve">Abstract</x> Recent studies have shown that lectins are promising tools for use in various biotechnological processes, as well as studies of various pathological mechanisms, isolation, and characterization of glycoconjugates and understanding the mechanisms underlying pathological mechanisms conditions, including the inflammatory response. This study aimed to purify, characterize physicochemically, and predict the biological activity of Canavalia oxyphylla lectin (CoxyL) in vitro and in vivo. CoxyL was purified by a single‐step affinity chromatography in Sephadex® G‐50 column. Sodium dodecyl sulfate polyacrylamide gel electrophoresis showed that the pure lectin consists of a major band of 30 kDa (α‐chain) and two minor components (β‐chain and γ‐chain) of 16 and 13 kDa, respectively. These data were further confirmed by electrospray ionization mass spectrometry, suggesting that CoxyL is a typical ConA‐like lectin. In comparison with the average molecular mass of α‐chain, the partial amino acid sequence obtained corresponds to approximately 45% of the total CoxyL sequence. CoxyL presented hemagglutinating activity that was specifically inhibited by monosaccharides (D‐glucose, D‐mannose, and α‐methyl‐D‐mannoside) and glycoproteins (ovalbumin and fetuin). Moreover, CoxyL was shown to be thermostable, exhibiting full hemagglutinating activity up to 60°C, and it was pH‐sensitive for 1 h, exhibiting maximal activity at pH 7.0. CoxyL caused toxicity to Artemia nauplii and induced paw edema in rats. This biological activity highlights the importance of lectins as important tools to better understand the mechanisms underlying inflammatory responses. Copyright © 2014 John Wiley & Sons, Ltd.